Estimation of water balance of Mahanadi catchment upto Hirakud dam site (1962-1966) by Thornthwaite's techniqu (MAUSAM, 1978)
A presentation of water balance of Mahanadi catchment upto Hirakud dam site by Thornthwaite’s method has been made. For this purpose values for the monthly water deficity, water surplus, soil moisture utilization and soil moisture recharge for the years from 1962 to 1966 have been tabulated and presented graphically.